Perbandingan Berbeda Alat Keamanan Untuk Mendeteksi Risiko Dalam Jaringan - Iriyanto, Muhammad (CV. Hawari, 2022)
Today, maintaining network security is a significant challenge. Data that has crossed a network is not regarded as secure. There are many risks, including snipping, phishing, spyware, hacking, and spoofing. Various network threats were covered in this article. There are numerous open-source technologies available to defend against these attacks. This study has examined tools like Acunetix and Intrusion Prevention System (IPS).